A Pathway for Advance Care Planning Co-Developed by Service Users and Interdisciplinary Healthcare Professionals in Older Persons Mental Health - Allen, Jennifer; Donnelly, Sarah; Murphy, Sinéad; Morton, Sarah (Age and ageing, 2024)
Background Advance Care Planning (ACP) has been recognised as an effective mechanism for decision-making, maintaining autonomy, and ensuring that end-of-life care is aligned with an individual’s will and preference. However, healthcare professional's (HCPs) lack of confidence and knowledge has been cited as a barrier to practice. Furthermore, there are currently no widely accepted guidelines for ACP in health service settings (Barnett et al., 2024[1]). A key aim of the second stage of a three-stage action research study was to co-design a pathway to support ACP practice in a Mental Health Service for Older Persons. Reference [1] Barnett, M.D., Bennett-Leleux, L.J. & Guillory, L.A. (2024) End-of-life treatment preferences and ACP among older adults, Death Studies, 48:2, 95-102. Methods The pathway was developed through cooperative inquiry (CI), a collaborative research approach. The CI group involved three service users (one with dementia family carer experience), and six interdisciplinary HCPs coming together as co-subjects and co-researchers. Five in-person CI meetings were convened. Results The CI group co-developed a person-centred pathway encompassing a tiered approach to ACP, which would be a source of guidance and support for service users, family carers and HCPs. Key components include training and education for HCPs to enhance confidence and skills; a Padlet online platform to host resources for service users and family carers; and facilitated interventions based on the individual needs of service users, including potentially additional accompanying documentation to capture mental health needs. An interdisciplinary approach to facilitating ACP engagement, with social work taking a lead role was also suggested. Conclusion The pathway was identified as an effective approach to embedding ACP practice in older persons mental health, through a tiered person-centred framework catering to the needs of both service users, and the training needs of staff. The pathway is proposed as potentially adaptable to other older persons services to support ACP engagement.